Сравнительная морфология выводящих протоков застенных желез пищеварительного канала некоторых растительноядных и хищных рыб - Коршунова, Л.А. (Вестник зоологии, 1971)
Anatomical and histological structure of excretory ducts of liver and pancreas wa s studied in the predatory Lucioperca lucioperca L. and phytophagous Ctenopharyngodon idella V a 1. It wa s found out that histological structure of biliary duct in predatory fish is similar to that in higher terrestrial vertebrates. The only distinction is that fish has no glands in biliary ducts. In phytophagous fish the wall of biliary duct consists mainly of striated musculature, in the predatory one s of smooth musculature. An assumption is made on arbitrary regulation of pancreas and bile enter intestine in phytophagous fish.